2022
DOI: 10.1186/s12888-022-03694-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening programs for common maternal mental health disorders among perinatal women: report of the systematic review of evidence

Abstract: Postpartum depression and anxiety are highly prevalent worldwide. Fisher et al., estimated the prevalence of depression and anxiety at 15.6% during the antenatal and 19.8% during the postpartum period. Their impact on maternal and child health is well-recognized among the public health community, accounting for high societal costs. The public health impact of these conditions has highlighted the need to focus on the development and provision of effective prevention and treatment strategies.In recent decades, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 58 publications
2
21
0
1
Order By: Relevance
“…La evidencia procedió de una revisión sistemática del tamizaje de problemas de salud mental frecuentes en las mujeres durante el embarazo el posparto (88), que incluyó seis estudios con un total de 13.728 mujeres. Uno de ellos fue un ECA (4621 mujeres), tres fueron ECA grupales (7930 mujeres) y dos fueron ensayos cuasi-ECA (5336 mujeres).…”
Section: Resumen De La Evidencia Y Consideracionesunclassified
“…La evidencia procedió de una revisión sistemática del tamizaje de problemas de salud mental frecuentes en las mujeres durante el embarazo el posparto (88), que incluyó seis estudios con un total de 13.728 mujeres. Uno de ellos fue un ECA (4621 mujeres), tres fueron ECA grupales (7930 mujeres) y dos fueron ensayos cuasi-ECA (5336 mujeres).…”
Section: Resumen De La Evidencia Y Consideracionesunclassified
“…Routine screening for PNDA using a validated tool facilitates a standardised approach to screening, which is central to fostering a reliable and consistent method of PNDA identification (and management) for all women, regardless of their socio‐economic status. Moreover, use of a validated tool improves detection as well as referral and service utilisation by women (Reilly et al, 2020 ; Waqas et al, 2022 ; van der Zee‐van den Berg et al, 2017 ), and is associated with improved maternal mental health outcomes (O'Connor et al, 2016 ; Reilly et al, 2020 ). In a recent systematic review of randomised controlled trials involving postpartum or pregnant women, O'Connor et al ( 2016 ) found as much as 9% absolute risk reduction in depression prevalence at 3–5 months follow‐up among women who were screened, compared to those not screened routinely.…”
Section: Introductionmentioning
confidence: 99%
“…Given the global prevalence of maternal mental ill health and the alarming expansion in numbers of those experiencing greater parental stress, isolation and mental illness in the shadow of COVID-19 ( 171 , 172 ), the increasing numbers of previously undiagnosed cases of maternal depression emerging through the implementation and expansion of routine screening procedures ( 173 , 174 ), and the profound inter-generational consequences of poor quality parenting, this refined, highly appreciated and effective Acorn program model offers the potential to strengthen the mental health system's response for a diversity of families. However, it is still the case that many families living in rural and remote areas may be restricted from participating in a program that congregates mothers and children at the same geographical venue.…”
Section: Discussionmentioning
confidence: 99%